Factors of eco driving practices among UUM students - Aziz, Zulkufli; Ramli, Noramira; Chik, Nurmaya; Jamaluddin, Hamizah Nadiah (2015)
Eco-driving is one of the important factor nowadays that need to focus on quality of life in a community whether the economic, social and environmental systems that providing a healthy, productive, meaningful life for all community, present and future. Clearly, eco-driving is one of the alternatives of a driving style to be much more economically, ecologically and can significantly reduce fuel consumption and carbon dioxide emission.This paper presents the significance of educating the drivers about eco-driving as well as the information about the factors of eco-driving that involve environmental impact, behavior and cost saving which may influence the driver‟s decision.By using quantitative method, questionnaire is being distributed among 400 respondents of UUM students. In conclusion, this research will encourage on preserving the environment while also maintaining personal mobility.